2017
DOI: 10.4274/tjcd.26779
|View full text |Cite
|
Sign up to set email alerts
|

Literature Review: Profile of Publications for the Patients with Stoma in Turkey

Abstract: REVIEWAmaç: Ülkemizde stomalı bireylerle yapılan araştırmaların ve bu alandaki yayınların niceliksel ve niteliksel olarak incelemek ve yapılacak yeni çalışmalara ışık tutarak stomalı bireylere yönelik bakımın kalitesini arttırmaya katkı sağlanmasıdır. Yöntem: Dokuz Eylül Üniversitesi abone elektronik veri tabanları (n=71), ULAKBİM (Ulusal Akademik Ağ ve Bilgi Merkezi) Ulusal Veri Tabanı, Pubmed, Ulusal Tez Merkezi, Google Akademik, kongre web siteleri, ulaşılabilen kongre/sempozyum kitapları ve makalelerin ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
2
0
1
Order By: Relevance
“…It was determined that mothers came to the fore in caring for children with colostomy, while fathers were relatively indifferent to care, citing various negativities. Vural et al (2016) found that patients had di culties due to frequent bag changes [30]. The results obtained from this study are very similar to those of the study by Vural et more than ve times a day [14].…”
Section: Cultiessupporting
confidence: 88%
“…It was determined that mothers came to the fore in caring for children with colostomy, while fathers were relatively indifferent to care, citing various negativities. Vural et al (2016) found that patients had di culties due to frequent bag changes [30]. The results obtained from this study are very similar to those of the study by Vural et more than ve times a day [14].…”
Section: Cultiessupporting
confidence: 88%
“…Complications of the stoma may occur due to surgical intervention, underlying pathology, insufficient preoperative, and postoperative treatment and care. 2,3,4 Complications related to stoma can be a dull discomfort or a severe life-threatening problem. Complications are classified as early and late complications depending on the time of occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…The tools with proven validity and reliability for the monitoring of stoma complications are limited in Turkey. 3 The Pittman Ostomy Complicity Severity index (OCSI) was developed by Joyce Pittman to identify and assess the severity of complications during the follow-up period (30 days postoperatively) of patients with a stoma. 4 This study aimed to evaluate the validity and reliability of the Turkish version of OCSI, which was prepared originally in English for patients with a stoma.…”
Section: Introductionmentioning
confidence: 99%
“…Yapılan başka bir çalışmada, stomalı bireyler kendi bakımlarını yapmada zorlandıklarını, giyinme, beslenme, uyku, banyo gibi aktivitelerinin değiştiğini belirtmişlerdir. 22 Olgu ile yapılan ilk görüşme sırasında kolostomi torbasının dolu olduğu ve sızdırdığı saptandı. Olgunun eğitim almadığı için boşaltma ve torba değişimi hakkında ne yapacağını bilmemesi nedeni ile anksiyete yaşadığı belirlendi.…”
unclassified